Partnership between Madrasah Aliyah and Balai Latihan Kerja (BLK) in Enhancing Graduates' Work Readiness: A Case Study of MA Miftahul Falah and BLK Pandaan - Novi Ariyanti; Maulidia Amirul Aulia (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2026)
Islamic Senior High Schools (Madrasah Aliyah) often face challenges in preparing graduates with competitive work skills due to a curriculum dominated by academic and religious subjects. This study aims to analyze the collaborative partnership between MA Miftahul Falah and the Pandaan Balai Latihan Kerja (BLK) in enhancing graduates' work readiness. Unlike previous studies that generally focus on vocational high schools (SMK), this research specifically examines the madrasah–BLK partnership from the perspective of Islamic education management, an aspect rarely explored in the existing literature. Employing a qualitative case study design, data were collected through in-depth interviews, observation, and documentation. The findings reveal that the partnership operates through a "Self-Funded" (Swadana) model in response to the madrasah's internal facility limitations, contributing foundation-level readiness through certification and technical skill enrichment. However, its effectiveness remains constrained by structural barriers, including a limited training duration (40 lesson hours), equipment shortages, and a competency gap between students' initial skills and industrial standards. The partnership currently remains at an operational-transactional level; thus, early curriculum synchronization and stronger multi-stakeholder involvement are needed to develop it into a strategic-integrative partnership that more effectively produces competitive, work-ready graduates.